Question Number 200262 by sonukgindia last updated on 16/Nov/23 | ||
![]() | ||
Answered by Frix last updated on 17/Nov/23 | ||
![]() | ||
$$\mathrm{I}\:\mathrm{get}\:\frac{{a}}{{b}}=−\mathrm{1}+\sqrt{\mathrm{2}+\mathrm{2}\sqrt{\mathrm{2}}}\approx\mathrm{1}.\mathrm{19737} \\ $$ | ||
Answered by mr W last updated on 17/Nov/23 | ||
![]() | ||
$$\frac{{a}+\sqrt{\left({a}+{b}\right)^{\mathrm{2}} +{b}^{\mathrm{2}} }+\sqrt{\mathrm{2}}\left({a}+{b}\right)}{{a}}=\frac{{b}+\sqrt{\left({a}+{b}\right)^{\mathrm{2}} +{b}^{\mathrm{2}} }+\left({a}+{b}\right)}{{b}} \\ $$$${let}\:\lambda=\frac{{a}}{{b}} \\ $$$$\lambda^{\mathrm{2}} −\left(\sqrt{\mathrm{2}}−\mathrm{1}\right)\lambda−\sqrt{\mathrm{2}}=\left(\mathrm{1}−\lambda\right)\sqrt{\lambda^{\mathrm{2}} +\mathrm{2}\lambda+\mathrm{2}} \\ $$$$\left(\sqrt{\mathrm{2}}−\mathrm{1}\right)\lambda^{\mathrm{2}} +\mathrm{2}\left(\sqrt{\mathrm{2}}−\mathrm{1}\right)\lambda−\left(\mathrm{3}−\sqrt{\mathrm{2}}\right)=\mathrm{0} \\ $$$$\Rightarrow\lambda=\frac{{a}}{{b}}=\sqrt{\mathrm{2}\left(\sqrt{\mathrm{2}}+\mathrm{1}\right)}−\mathrm{1}\:\checkmark \\ $$ | ||